Design and Characterization of Timolol Loaded Gellan Gum Nanoparticles for Improved Ocular Drug Delivery - Kandav, Gurpreet; Lochab, Anjali Kumari; Sharma, Tamanna (Indian Journal of Pharmaceutical Education and Research, 2024)
Aim Glaucoma treatment often involves the topical application of Timolol maleate (TM) to the eye. However, achieving the desired bioavailability via the ocular route can be challenging due to poor retention and penetration of the drug. To address this issue, Gellan Gum (GG) polymer was employed in the current research to formulate nanoparticles of TM to enhance its release during ocular delivery. Materials and Methods TM loaded GG Nanoparticles (TMNPs), were formulated by ionotropic gelation method. The study involved the fabrication of different experimental batches of TMNPs, with varying concentrations of gellan gum (0.06% and 0.12%) and aluminium chloride (0.01,0.02, and 0.03%) and evaluating the impact of these concentrations on the particle size and Entrapment Efficiency (EE%), of TMNPs. The optimized batch of prepared TMNPs was further evaluated for different parameters such as DSC, SEM, FTIR, in vitro release, and ex vivo tolerance and permeation studies. Results The particle size and EE% of different batches of TMNPs were found to be in the range of 135.2 to 1519 nm and 20.51 to 78.56% respectively. TMNPs showed a prolonged in vitro drug release (62.11%) profile for 12 hr. Ex vivo ocular tolerance studies confirmed the TMNPs to be non-irritant and safe for ocular drug delivery. Permeation studies revealed that a higher amount of TM from TMNPs (1.9 fold) was taken up by goat’s cornea as compared to drug solution. Conclusion In conclusion, TMNPs are found to depict sustained release and can be considered potential and safe carriers for the ocular drug delivery of TM.
Keywords: Nanoparticles; Glaucoma; Timolol maleate; Gellan gum; Biopolymer